CONTENT OF PREPARING FUTURE GEOGRAPHY TEACHERS TO USE PROJECT TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2025)
This article discusses the theoretical foundations for preparing future geography teachers to utilize project technologies in the educational process. It examines the methodological system for training future geography teachers in the use of project technologies and evaluates the effectiveness of this preparation. Additionally, the content of preparing future geography teachers to use project technologies in the educational process is analyzed.